Synthesis of Hydroxyapatite From Chicken Bones Using the High Temperature Method - Riyanda Bagus Setiawan; Faishal Zhafran Mumtaz; Lilik Suprianti; Ramadhani Mahendra Kusuma (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study investigates the syntesys of hydroxyapatite (HAp) from chicken bone waste, which is abundantly available due to high poultry production, using a high-temperature method. The objective of this study was to determine the effect of variations in sintering temperature (300, 400, 500, and 600°C) and sintering time (3, 4, 5, 6, and 7 hours) on the yield and Ca/P ratio of the HAp produced. The prepared chicken bone powder was first calcined at 900°C for 3 hours before sintering. The results showed that the optimal conditions were 600°C for 7 hours, characterized by a change in the sample's colour to white and a yield of 69%. XRF analysis confirmed the formation of HAp with a Ca/P ratio of 1.69. It was concluded that a sintering temperature of 600°C for 7 hours is optimal for producing pure HAp from chicken bone waste. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production